Construção de um vírus Vaccínia Ankara Modificado (MVA) Recombinante expressando a proteína e do vírus Dengue 3 - Thiago Campolina Diniz (2009)
Dengue is now the subject of the largest public health campaign in Brazil and is present in 27 states of the Federation. However, because the campaigns to combat the vector have been historically unsuccessful, the development of an antidengue vaccine, yet non-existent, is the safest option for the control of this urban arbovirus disease. The MVA virus belongs to the Poxviridae family, if used as a viral vector in antidengue immunization, has many advantages such as: being unable to multiply in mammalian cells, easy methods of construction, its genetic manipulation is relatively simple, based mainly on the phenomenon of homologous recombination, its genome supports the introduction of enormous quantities of exogenous DNA, proteins produced are processed and transported in a way similar to that happens in the origin cells from the gene studied, among others. Here, we report the construction of a recombinant monovalent vaccine against the Dengue virus serotype 3, the serotype more prevalent in Brazil. The E protein is the largest and the main protein of the viral envelope, and also the main target for neutralizing antibodies, which shows the great potential that this protein may have in recombinant vaccine building. We obtained a Dengue E cDNA and subsequently inserted it into a shuttle plasmid. Chicken embryo Fibroblast cells (CEFs) were inoculated with MVA and transfected with the shuttle plasmid, allowing for homologous recombination between the virus and plasmid. The obtained recombinant virus was able to express the E protein of Dengue virus serotype 3, as demonstrated by the western blot.